1980
DOI: 10.1021/bi00561a003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a physiological role of corticosteroid binder IB

Abstract: Glucocorticoid binding proteins in liver and kidney of adrenalectomized rats have been analyzed by rapid ionexchange chromatography, gel filtration, and specific interactions with antibodies against purified liver cytosol receptor and purified transcortin. In both tissues, the unactivated form of the [3H]triamcinolone acetonide-receptor complex is eluted by 0.4-0.5 M KC1 from DEAE-Sephadex minicolumns. After heat activation, the major form in liver cytosol, corticosteroid binder II, is eluted by 0.2 M KC1 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…More recently, this difference has been confirmed by the use of dexamethasone, which has a -greater specificity of binding than cortisol, and it was also observed that BIO.A(2R) mice have a higher level of cytosolic receptor than do BlO.A(4R) or B1O.A (5R) (26). It has also been shown that this strain difference could not be demonstrated in liver (27), which is in agreement with observations of tissue-specific variation in cortisol receptors in rats (28). However, the biochemical events that control palatal closure could be very complex, and it is by no means clear whether an H-2-linked effect on glucocorticoid receptors will account for the genetic differences in cleft palate susceptibility.…”
Section: Resultssupporting
confidence: 83%
“…More recently, this difference has been confirmed by the use of dexamethasone, which has a -greater specificity of binding than cortisol, and it was also observed that BIO.A(2R) mice have a higher level of cytosolic receptor than do BlO.A(4R) or B1O.A (5R) (26). It has also been shown that this strain difference could not be demonstrated in liver (27), which is in agreement with observations of tissue-specific variation in cortisol receptors in rats (28). However, the biochemical events that control palatal closure could be very complex, and it is by no means clear whether an H-2-linked effect on glucocorticoid receptors will account for the genetic differences in cleft palate susceptibility.…”
Section: Resultssupporting
confidence: 83%
“…observed, it appeared to be due to limited receptor proteolysis (Wrange & Gustafsson, 1978;Carlstedt-Duke et al, 1979;Govindan, 1980;Govindan & Manz, 1980;Stevens & Stevens, 1981;Tsawdaroglou et al, 1981). However, in at least one instance (Litwack & Rosenfield, 1975;Markovic et al, 1980), a second species of glucocorticoid receptor, designated binder IB, which did not appear to be a proteolytic fragment of the major receptor form (binder II; Litwack et al, 1973), was found to occur in a tissue-specific fashion. In the present study, the activated receptor eluted as a single, symmetrical peak on all the columns tested, regardless of the activation method used.…”
Section: Discussionmentioning
confidence: 99%
“…Barnett & Star (1981), taking account of these problems, found a significant negative correlation between unbound plasma cortisol (free cortisol) and weight change in sheep; however, this was in a complex situation using recently parous sheep, some of which were suckling lambs. Second, the presence of high-affinity corticosteriod-binding components distinct from transcortin has been found in several tissues (Feldman et al 1973;Giannopoulus, 1973;Markovic et al 1980). Specifically, the presence of a skeletal-muscle glucocorticoid receptor has been shown in a variety of species, namely the rat (Mayer et al1974), pig (Snochowski et al 1981) and human.…”
mentioning
confidence: 99%